Can auscultatory blood pressure normative values be used for evaluation of oscillometric blood pressure in children? - Šuláková, Terezie; Šuláková, Astrida; Strnadel, Jiří; Pavlíček, Jan; Obermannová, Barbora; Feber, Janusz (Journal of clinical hypertension (Greenwich, Conn.), 2017)
The aim of the study was to analyze whether auscultatory normative values (Fourth Task Force [4TF]) can be applied to blood pressure (BP) obtained by oscillometric devices. The authors performed a retrospective analysis of oscillometric office BP and ambulatory BP monitoring in 229 children (116 boys), median age 15.31 years. Office systolic BP (SBP) and diastolic BP (DBP) values were converted into Z scores using 4TF and oscillometric (German Health Interview and Examination Survey for Children and Adolescent [KiGGS]) reference values. There was good correlation between the two normative methods (r=0.9773 for SBP, r=0.9627 for DBP). Results from Bland-Altman test revealed only minimal differences in Z scores between 4TF and KiGGS for SBP, but a significant proportional error for DBP. 4TF and KiGGS Z scores were equally predictive of ambulatory hypertension. In conclusion, auscultatory and oscillometric normative data are interchangeable for SBP but not for DBP.
Keywords: poslech; Oscillometry; Humans; Blood Pressure Determination; dítě; auscultatory normative values; Child; Female; children; lidé; Blood Pressure Monitoring, Ambulatory; ambulantní monitorování krevního tlaku; ženské pohlaví; krevní tlak; Male; Retrospective Studies; Auscultation; Adolescent; retrospektivní studie; blood pressure; mužské pohlaví; Blood Pressure; oscilometrie; měření krevního tlaku; mladiství; oscillometric normative values